Labeling graphene oxygen groups with europium - Ambrosi, Adriano (2015)
Graphene-related materials contain chemically bonded oxygen atoms in the form of epoxy, hydroxy, carboxy, and carbonyl groups. It is important to determine the quantity of oxygen atoms and to understand their position on the graphene sheet. However, visualization of these groups by standard methods is a challenge. Here, we utilize europium(III) as a selective label for oxygen-containing groups. We studied three different graphene-related materials: 1) graphene oxide, 2) chemically reduced graphene oxide, and 3) thermally reduced graphene oxide (the number of oxygen containing groups decreases from material 1 to 3). We show that it is possible to efficiently use Eu as a label of oxygen-containing groups. This Eu label could be applied to determine the precise location of oxygen-containing groups on graphene sheets and also induce novel optical, electrochemical, and catalytic properties.